What are the appropriate indicators of surgical difficulty during laparoscopic cholecystectomy? Results from a Japan‐Korea‐Taiwan multinational survey. (5th September 2016) - Iwashita, Yukio; Ohyama, Tetsuji; Honda, Goro; Hibi, Taizo; Yoshida, Masahiro; Miura, Fumihiko; Takada, Tadahiro; Han, Ho‐Seong; Hwang, Tsann‐Long; Shinya, Satoshi; Suzuki, Kenji; Umezawa, Akiko; et al.
Abstract: Background: Serious complications continue to occur in laparoscopic cholecystectomy (LC). The commonly used indicators of surgical difficulty such as the duration of surgery are insufficient because they are surgeon and institution dependent. We aimed to identify appropriate indicators of surgical difficulty during LC. Methods: A total of 26 Japanese expert LC surgeons discussed using the nominal group technique (NGT) to generate a list of intraoperative findings that contribute to surgical difficulty. Thereafter, a survey was circulated to 61 experts in Japan, Korea, and Taiwan. The questionnaire addressed LC experience, surgical strategy, and perceptions of 30 intraoperative findings listed by the NGT. Results: The response rate of the survey was 100%. There was a statistically significant difference among nations regarding the duration of surgery and adoption rate of safety measures and recognition of landmarks. The criteria for conversion to an open or subtotal cholecystectomy were at the discretion of each surgeon. In contrast, perceptions of the impact of 30 intraoperative findings on surgical difficulty (categorized by factors related to inflammation and additional findings of the gallbladder and other intra‐abdominal factors) were consistent among surgeons. Conclusions: Intraoperative findings are objective and considered to be appropriate indicators of surgical difficulty during LC. Abstract : Highlight Iwashita and colleagues report on their multinational survey designed to elucidate factors contributing to surgical difficulty during laparoscopic cholecystectomy. Commonly used indices such as duration of surgery are invalid to evaluate surgical difficulty. Instead, intraoperative findings are objective and appropriate indicators that should be universally used in future prospective studies.